1989
DOI: 10.1111/j.1439-0418.1989.tb00441.x
|View full text |Cite
|
Sign up to set email alerts
|

The parasite‐host relationship between Encarsia formosa Gahan (Hymenoptera, Aphelinidae) and Trialeurodes vaporariorum (Westwood) (Homoptera, Aleyrodidae)

Abstract: The greenhouse whitefly (Trialeurodes vaporariorum) is a pest insect on sweet pepper (Capsicum annuum) in Hungary, but not in the Netherlands. To examine the underlying mechanism for this difference, whitefly strains from both countries were tested on commonly used Hungarian and Dutch sweet‐pepper cultivars. The developmental rate from egg to adult, the survival rate of adults and the oviposition rate were measured. For all three parameters the Hungarian sweet‐pepper cultivar turned out to be a better host pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
(1 reference statement)
3
9
0
Order By: Relevance
“…This indicates that host selection does not occur before a host has been drummed, similar to those reported by van Lenteren et al (1976a) for the primary parasitoid E. formosa. Our observations that the L3 stage is the most preferred stage for hyperparasitization for E. tricolor is similar to information provided for E. tricolor by Avilla and Copland (1987).…”
Section: Searching and Parasitization Behaviour Of E Tricolorsupporting
confidence: 84%
“…This indicates that host selection does not occur before a host has been drummed, similar to those reported by van Lenteren et al (1976a) for the primary parasitoid E. formosa. Our observations that the L3 stage is the most preferred stage for hyperparasitization for E. tricolor is similar to information provided for E. tricolor by Avilla and Copland (1987).…”
Section: Searching and Parasitization Behaviour Of E Tricolorsupporting
confidence: 84%
“…Vet & van Lenteren (1981) and van Lenteren et al (1987) compared the longevity of E. formosa at different temperatures in the presence or absence of hosts reported by different authors, and concluded that being given access to hosts shortened adult longevity in E. formosa, but not in Eretmocerus species. In the present study adult longevity was shorter in the presence than absence of hosts in E. formosa D and the two Eremocerus species.…”
Section: Adult Longevitymentioning
confidence: 99%
“…Van Lenteren et al (1987) studied the effect of host quality on adult longevity of E. formosa, and discovered a longer longevity when all instars of T. vaporariorum larvae were present during the test, than …”
Section: Adult Longevitymentioning
confidence: 99%
“…Food is also an important factor for parasitoid survival, and it is essential to ensure mating and subsequent for aging and oviposition of the parasitoid (van Lenteren et al, 1987;Finch & Coaker, 1969). Adult A. kamali that were provided with food lived approximately 20 times longer than unfed individuals.…”
Section: Longevity Testmentioning
confidence: 99%